SISTEM INFORMASI AKADEMIK PONDOK PESANTREN TAHFIDZUL QUR’AN NURUL KHOIR JAMBI BERBASIS WEB - simorangkir, lucy; Rudi Yaman, Maman (LP2M Universitas Nurdin Hamzah, 2023)
Academic Information System (SIAKAD) is an application that integrates all the main processes of an Education business, into an information system supported by information technology. At the Tahfidzul Qur'an Islamic Boarding School NurulKhoir Jambi for the academic system and information delivery still use a manual system, so the delivery of information is rather slow to the public and students, for this reason a new system is needed, namely the Tahfidzul Qur'an Islamic Boarding School Academic Information System NurulKhoir Web-Based Jambi with php programming language and MySQL database. In building this Web-based Academic Information System, there are several input requirements, namely user data, tuition payment data, news data, educator data, student data, curriculum data, subject data, schedule data, learning method data, registration requirements data. For process needs such as student page processes, educator page processes and other processes. For output needs such as tuition payment data reports, student data reports, and value data reports. With this system, the public can more easily get information and provide advice to the Tahfidzul Qur'an Islamic Boarding School NurulKhoir Jambi, and it is hoped that this system will make it easier for the community and students, as well as the Tahfidzul Qur'an Islamic Boarding School NurulKhoir Jambi.